Disparities in health burden, health-care facilities, and resources among countries in China's Belt and Road Initiative: a mixed methods study. (December 2017) - Wang, Youfa; Zhou, Zhongliang; Zhao, Yaling; Bai, Ruhai; Wang, Xing; Sun, Xiaomin; Qu, Weidong; Wang, Yaogang; Yan, Hong
Abstract: Background: In 2015, China launched the Belt and Road Initiative (BRI; also known as the Silk Road Economic Belt and the 21st-Century Maritime Silk Road), a trade and infrastructure network to promote international collaboration. We aimed to compare health burden, health-care facilities, and resources among countries participating in the BRI, to help understand health needs, develop health promotion programmes, and facilitate collaboration on global health. Methods: In a mixed methods study, data from 1990 to 2015 were collected from the WHO, UN, and World Bank database for key health indicators and social, economic, and environmental factors (eg, gross domestic product) for China and 65 other countries participating in the BRI. We used linear and logistic regression and multilevel models in the analysis, examining impact associations of the selected health indicators and social, economic, and environmental factors. Findings: We noted large variation and shifts over time in patterns of disease burden, availability of health-care facilities (eg, numbers of doctors, nurses, hospitals, and beds), and context factors across the 66 countries. During 2000–14, life expectancy increased in almost all countries except for Iraq and Syria, by 3·9 years on average. Life expectancy was positively associated with gross domestic product per person, stronger in higher quintiles. Since 1990, mortality in children younger than 5 years has declined by 74%, from 62 deaths per 1000 livebirths in 1990 to 16 per 1000 livebirths in 2015, an annual fall of 3·0%. Economic, social, and environmental factors were closely associated with health indicators and health-care facilities and the disparities in them. Interpretation: Large variations exist in disease burden, availability of health-care facilities, and economic, social, and environmental factors across the BRI countries. This initiative provides good opportunities to study the effect of context factors and international collaboration on health outcomes. Funding: Chinese Medical Board (GNL 16-262), Xi'an Jiaotong University.